Physical and mechanical properties of recycled aggregate concrete with ground granulated blast furnace slag - Cakir, Ozgur; Sayaca, Selin (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2021)
Considering the size of the construction industry in our country and the insufficient quality control, it is necessary to establish and develop the recycled aggregate (RA) sector in our country in order to evaluate the concrete extracted / to be released during the improvement and demolition works of the urban transformation processes in the current and future urban transformation process. In this experimental study, in which the usability of RA with ground granulated blast furnace slag (GGBFS) (0-15-30%) in concrete production was investigated; physical and mechanical tests were carried out on concrete samples containing natural aggregate and RA at the 7th, 28th and 90th days. For natural aggregate series; concrete with a water/binder ratio of 0.50, 380 doses, expected to be exposed to XS1 effect class and target strength C30/37 was produced using natural aggregates. In the production of series containing RA; the recycled aggregates taken from the recycling facility were brought to the same granulometry as the natural aggregates and concretes with the same dosage and the same water / binder ratio were produced. Unit weight, workability (slump) and air content tests in fresh concrete; unit weight, compressive strength, split tensile strength, ultrasonic pulse velocity test, capillary water absorption and volumetric water absorption tests on hardened concrete were performed. The results obtained show that coarse and fine natural aggregates can be used both physically and mechanically by replacing them with RA at high rates by using GGBFS. The performance of concrete series containing RA with 30% GGBFS is better than natural aggregate concrete series, especially at the 28th and 90th days.
Keywords: Construction and demolition waste; recycled aggregate concrete; ground granulated blast furnace slag; physical properties; mechanical properties; SILICA FUME; BEHAVIOR; Engineering